Um estudo sobre a estabilidade e bifurcação de Hopf no sistema mecânico de Watt - Viana, Juliana Lázara Curcino (2009)
In this work we give the analysis did by Sotomayor et al in [11], on stability and Hopf bifurcation of the Watt Mechanical System. This system consists of a steam engine coupled to a Watt Regulator. From this analysis are obtained several results on the onset of Hopf Bifurcation. Indeed, it is showed that if a special expression, which depends on the physical parameters of this system, is positive or negative the existence of supercritical or subcritical Hopf bifurcation can be achieved from it.